Integrasi Model Pembelajaran Berbasis Masalah Berbantuan Simulasi Digital untuk Meningkatkan Keterampilan Analisis Siswa: Literature Review - Jayanti Noor Purbo Rukmi; Muhibuddin Fadhli; Citra Kurniawan; Made Duananda Kartika Degeng (Postgraduate, University of Mataram, 2025)
This study aims to determine the effectiveness of implementing a digital simulation assisted Problem-Based Learning model in improving students’ analytical skills, to determine research trends regarding the integration of digital simulation assisted Problem-Based Learning in learning process, and to determine the contribution of digital simulation assisted Problem-Based Learning to improving students’ analytical skills. This study uses the Systematic Literature Review (SLR) method and data collection is assisted by bibliometric analysis. Data were obtained using Google Scholar, Research Rabbit, Research Gate, and Springer. Reference articles are taken from 2020-2025. The results of the study that digital simulation is closely related to the Problem-Based Learning model. Where the integration of these two strategies can increase learner creativity in developing knowledge. Improved analytical skills occurred after the use of digital simulation in learning. this improvement occurs because the use of digital simulations can make the learning process more effective, more attractive, instructive, and visually more interactive presentations so that they can attract learners and help improve learning outcomes. Research on problem-based learning using digital simulations is still very limited. However, several schools in Indonesia have begun implementing this model and media by utilizing PhET simulations in science learning, such as physics, chemistry, and biology.